Bone mineral density of rat femurs after hindlimb unloading and different physical rehabilitation programs - Barbosa,Adelton Andrade (2011)
Bone weakening can occur due to the absence of load on the skeleton or even short periods of decreased physical activity. Therefore, musculoskeletal diseases that involve temporary immobilization by casts, inactivity or tension increases the risk of fractures. Physical activity is the most studied procedure both to prevent damage and to restore bone structure. The present study aimed at evaluating, by bone densitometry on rat femurs, the influence of hindlimb unloading and later running activity on treadmill or free movement. Sixty-four Wistar rats were used, aged 65 days with a mean corporal mass of 316.11g, randomly divided into eight experimental groups: group 1, the suspended control with seven animals under hindlimb unloading regimen for 28 days, then euthanized; groups 2 and 3, the trained suspended comprising of 7 and five animals, respectively, subjected to hindlimb unloading for 28 days, followed by treadmill exercise for 28 days (group 2) or 56 days (group 3), then euthanized; groups 4 and 5, designated free suspended, comprised of 7 animals each under hindlimb unloading regimen for 28 days followed by free activity in cages for 28 days (group 4) or 56 days (group 5), then euthanized; groups 6, 7 and 8, negative controls, each with 8 animals allowed to free activity in cages and euthanized at the ages of 93, 121 and 149 days, respectively. Bone mineral density (BMD) of the left femur was analyzed by bone densitometry. Unloading by tail-suspension decreased BMD while treadmill training and free activity in cages promoted its recovery in a similar way and over time.